FRI0018 Targeted inhibition of janus kinases abates IFN-GAMMA-INDUCED invasive behavior of fibroblast-like synoviocytes. (15th June 2017) - Karonitsch, T; Beckmann, D; Dalwigk, K; Byrne, R; Niederreiter, B; Holinka, J; Sevelda, F; Korb-Pap, A; Steiner, G; Smolen, J; Pap, T; Kiener, H
Abstract : Background: Emerging evidence suggests that fibroblast-like synoviocytes (FLS) are key effector cells in rheumatoid arthritis (RA) and research into the mechanisms defining FLS activity in RA indicate that cytokines secreted by leukocytes play a crucial role. Nevertheless, the contribution of IFNγ, which is increased in rheumatoid synovitis, to the inflammatory synovial tissue reaction is not known. Objectives: To explore the function of the T-cell cytokine IFNγ for mesenchymal tissue remodeling in RA, and to determine whether IFNγ-signaling controls the invasive potential of FLS. Methods: To assess architectural responses, FLS were cultured in three-dimensional micromasses. FLS motility was analyzed in migration-, spreading- and invasion assays. Signaling events relevant to cellular motility were defined by western blots. Baricitinb and siRNA pools were used to suppress Janus Kinase (JAK) functions. Results: Histological analyses of micromasses revealed unique effects of IFNγ on FLS shape and tissue organization. This was consistent with accelerated migration, pronounced actin and focal adhesion (FA) re-organization upon IFNγ stimulation. Since actin and FA dynamics and, thus, cell motility are integrated by the focal adhesion kinase (FAK), we next analyzed its activity. Indeed, IFNγ stimulation induced the phosphorylation of FAK-Y925, a phosphosite implicated in FAK-mediated cell migration. siRNA knockdown of JAK2, but not JAK1, abrogated FAK activation by IFNγ. Correspondingly, IFNγ-inudced FAK activation and invasion of FLS was abrogated by the JAK-inhibitor baricitinib. Conclusions: Our study contributes insight into the synovial response to IFNγ and reveals JAK2 as a potential therapeutic target for FLS-mediated joint destruction in arthritis, especially in RA. Disclosure of Interest: None declared